Islamophobia - Moten, Abdul Rashid (Oxford University Press, 2014)
Islamophobia is the “shorthand way of referring to the dread or hatred of Islam and, therefore, to fear or dislike all or most Muslims” based upon an “unfounded hostility towards Islam.” This is the definition set out in the influential report Islamophobia: A Challenge for Us All (Runnymede Trust, 1997, p. 1), also known as the Runnymede report, and is the definition that has shaped and influenced most of the understandings of the term, although the term remains contested and is sometimes used interchangeably with neo-Orientalism, anti-Muslimism, anti-Muslim racism, or “new” or cultural racism. Much debate has surrounded the use of the term, questioning its adequacy as an appropriate and meaningful descriptor. However, since Islamophobia has broadly entered the social and political lexicon, arguments about the appropriateness of the term now seem outdated. ......